Geological map of Jutulsessen (Dronning Maud Land) - Elvevold, Synnøve; Engvik, A K; Hansen, C; Jacobs, J; Meiklejohn, I; Myhre, P I; Rudolph, E (Norsk Polarinstitutt, 2021)
Publication Title: Temakart; 54 Place: Tromsø
Keywords: Dronning Maud Land; geologi; kart

The Mapping of Antarctica - Pedersen, Jakob Søndergård; Curtis, Philip (The Map House, 2012)
Keywords: Antarktis; ekspedisjoner; kart; kartlegging; kartografi; oppdagelsesreiser

Geological map of Heimefrontfjella, Dronning Maud Land, Antarctica (Scale 1:250,000) - Jacobs, Joachim; Bauer, Wilfried; Kreutzer, Stefan; Patzelt, Gernot; Schmidt, Rainer; Schulze, Peter; Siegesmund, Siegfried; Spaeth, Gerhard; Thomas, Robert J; Weber, Klaus; Zarske, Gerd (PANGAEA, 2009)
The geological overview map was compiled from 15 geological maps (1 : 25,000) and is based on Jacobs et al. 1996. The topographic basemaps were adapted from unpublished 1:250,000 provisional topographic maps, Institut f. Angewandte Geodäsie, Frankfurt, 1983. Part of the contour lines are from Radarsat (Liu et al. 2001).
Keywords: Dronning Maud Land; geologi; kart; topografi

Antarktis geografi = Antarctic geography - Paulsen, Harald B (Norsk hvalfangst-tidende, 1936)
Keywords: Antarktis; geografi; kart; kartlegging; litteratur

Antarktis - Walnum, Ragnv. (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1932)
Publisher: Routledge
Keywords: Sørishavet; hvalfangere; isforholdene; isgrenser; iskartet; kart; pakkis

Polarområdene : utforskning, næringsinteresser, opdeling - Isachsen, Fridtjov (Cappelens verdensatlas)
Keywords: Antarktis; kart; polarområdene